1988
DOI: 10.1021/bi00402a031
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of recombinant hepatitis B surface antigen protein by mass spectrometry

Abstract: The primary structure of recombinant hepatitis B surface antigen protein produced in yeast has been confirmed by mass spectrometric peptide mapping. These studies corroborate more than 85% of the amino acid sequence derived by sequencing of the gene and identified the presence of an acetyl moiety on approximately 70% of the NH2-terminal methionine residues. Prior to the present work, direct structural analysis was largely prevented by the insolubility of this integral membrane protein and its primary degradati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 31 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…The 3'-tailed 11-mer ODNs were prepared with a sequence complementary to the initiation codon region of the mRNA for the hepatitis B surface antigen protein (33). The 20-mer ODN target chosen for the Tm studies provides nucleotide overhangs that may influence interactions with the 3'-modification.…”
Section: Resultsmentioning
confidence: 99%
“…The 3'-tailed 11-mer ODNs were prepared with a sequence complementary to the initiation codon region of the mRNA for the hepatitis B surface antigen protein (33). The 20-mer ODN target chosen for the Tm studies provides nucleotide overhangs that may influence interactions with the 3'-modification.…”
Section: Resultsmentioning
confidence: 99%
“…Manual and Automated Edman Degradation. Manual Edman degradation was performed on mixtures of peptides as previously described (Hemling et al, 1988). Automated Edman degradation was carried out with a Beckman System 890 M-2 sequencer with HPLC identification and quantitation of PTH-amino acids performed as previously described (Hawke et al, 1982).…”
Section: Methodsmentioning
confidence: 99%
“…Original data published by GSK (Stephenne 1990) indicated consistent levels of lipid (11-15 mcg per 20 mcg protein), sugars (0.2-0.35 mcg per 20 mcg protein), antigen using a radioimmunoassay called AUSRIA (Abbott_Diagnostics 2012), and protein purity (>98 %) in the bulk product. Further structural studies of the vaccine (Hemling et al 1988) confirmed 85 % of the sequence by FAB mass spectrometry of proteolytic and CNBr digests. Complete structure confirmation was thwarted by the fact that the protein was 70 % blocked at its N-terminus and contained very hydrophobic sequences making handling of the protein difficult.…”
Section: Characterization Of the Recombinant Hbv Vaccinesmentioning
confidence: 80%